A Transfer Learning Radiomics Nomogram for Preoperative Prediction of Borrmann Type IV Gastric Cancer From Primary Gastric Lymphoma - Feng, Bao; Huang, Liebin; Liu, Yu; Chen, Yehang; Zhou, Haoyang; Yu, Tianyou; Xue, Huimin; Chen, Qinxian; Zhou, Tao; Kuang, Qionglian; Yang, Zhiqi; Chen, Xiangguang; et al. (Frontiers in Oncology, 2022)
Objective This study aims to differentiate preoperative Borrmann type IV gastric cancer (GC) from primary gastric lymphoma (PGL) by transfer learning radiomics nomogram (TLRN) with whole slide images of GC as source domain data. Materials and Methods This study retrospectively enrolled 438 patients with histopathologic diagnoses of Borrmann type IV GC and PGL. They received CT examinations from three hospitals. Quantitative transfer learning features were extracted by the proposed transfer learning radiopathomic network and used to construct transfer learning radiomics signatures (TLRS). A TLRN, which integrates TLRS, clinical factors, and CT subjective findings, was developed by multivariate logistic regression. The diagnostic TLRN performance was assessed by clinical usefulness in the independent validation set. Results The TLRN was built by TLRS and a high enhanced serosa sign, which showed good agreement by the calibration curve. The TLRN performance was superior to the clinical model and TLRS. Its areas under the curve (AUC) were 0.958 (95% confidence interval [CI], 0.883–0.991), 0.867 (95% CI, 0.794–0.922), and 0.921 (95% CI, 0.860–0.960) in the internal and two external validation cohorts, respectively. Decision curve analysis (DCA) showed that the TLRN was better than any other model. TLRN has potential generalization ability, as shown in the stratification analysis. Conclusions The proposed TLRN based on gastric WSIs may help preoperatively differentiate PGL from Borrmann type IV GC. Borrmann type IV gastric cancer, primary gastric lymphoma, transfer learning, whole slide image, deep learning.